POLITENESS AND IMPOLITENESS IN CINDERELLA (2015): A PRAGMATIC ANALYSIS - Anissa Eka Meilani; Agus Wijayanto (SOSIOEDUKASI, 2026)
Recent discourse in pragmatic studies has contested the idea that politeness functions solely as a cooperative and harmony-seeking endeavor, particularly in contexts characterized by unequal power relations. This research investigates the functions of politeness and impoliteness as instruments of control in hierarchical interactions. This study utilizes Brown and Levinson's politeness theory, Culpeper's impoliteness framework, and multimodal discourse analysis to investigate the collaborative construction of dominance through linguistic and non-verbal resources in cinematic discourse. Utilizing a qualitative descriptive methodology, the analysis examines specific subtitle dialogues between Lady Tremaine and Cinderella in the film Cinderella (2015), enhanced by multimodal indicators including gaze, intonation, facial expressions, and camera angles. The analysis focuses on important pragmatic factors, such as indirectness, sarcastic politeness, and actions that put someone's face in danger. The results show that people use politeness on purpose to make authority seem real, control behavior, and make domination seem normal. Being rude, on the other hand, strengthens hierarchical control through both words and actions. These findings indicate that politeness in power-laden discourse cannot be interpreted merely as cooperative behavior; it necessitates analysis as a strategic and multimodal practice. The study underscores the importance of extending pragmatic analysis beyond verbal interaction and integrating multimodal perspectives as a best practice in the analysis of power and control in discourse.